Correlation dependences of morphological indices of the tissue state in the hip joint in case of its diseases, complicated with the femoroacetabular conflict - Hryhorovskyi, Valeriy; Filipchuk, Victor; Kаbаtsiy Myroslav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The purpose of the present research was to detect pathomorphological changes in tissues of the hip joint, which were accompanied with femoroacetabular impingement (FAI) syndrome, as well as to reveal correlation dependences between morphological indices on the basis of graded quantification of the intensity of pathological changes and their frequency analysis. The material of the study consisted of 65 biopsies of the hip joint tissues (the proximal femoral epimetaphysis, acetabulum, acetabular lip and articular capsule), which were obtained during corrective interventions for different diseases (aseptic femoral head necrosis, juvenile epiphyseolysis of the femoral head, hip joint dysplasiae) and, according to data of clinical visualization methods, were accompanied with FAI syndrome. Various pathological changes were revealed; these manifested themselves with discirculatory, chronic dystrophic-destructive and inflammatory processes in tissues of the femoral head, neck, acetabulum and articular capsule. The above processes were detected with different frequency and had unequal parameters of correlation dependences between some graded morphometric indices in different nosologies of hip joint lesions.